Knowledge and home management of diarrhoeal disease among mothers with under-five children attending university of Uyo teaching hospital, Nigeria - Dr. Mkpouto Udeme Akpan; Dr. Echey Ijezie (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Diarrhoea is a major cause of mortality in under-five children worldwide, but more especially in developing countries including Nigeria. Most of the deaths are due to dehydration and its mismanagement at home. Mothers’ good knowledge and proper home management will help reduce its morbidity and mortality rates. Aim: To assess the knowledge of diarrhoea and home management among mothers with under-five children attending the University of Uyo Teaching Hospital, Uyo, Nigeria. Methods: A twenty-two item structured questionnaire was administered to 370 mothers with at least one under-five child who attended either the Children’s Emergency Unit or the Paediatric clinic of the University of Uyo Teaching Hospital. The questionnaire bordered on knowledge, prevention, home management and attitudes of mothers toward diarrhoea. Results: Majority (86.2%) of the women knew that drinking dirty water can cause diarrhoea, 175 (47.3%) believed teething causes diarrhoea, 177 (47.8%) knew that human faeces could be a source of diarrhoea, while 332 (89.7%) knew that hand-washing prevents one from developing diarrhoea. Their level of knowledge of signs of dehydration was low with 45.7%, 62.4%, 27.8% and 42.2% identifying sunken eyes, thirst and dry mouth, tearless eyes and loss of stretchiness of the skin as signs of dehydration respectively. Conclusion: Though mothers had good knowledge of causes, and home management of diarrhoea, there are still knowledge gaps. Efforts to bridge the gaps should be tackled through periodic and regular health education programs for the mothers